Heat-conducting glue as well as preparation process and application thereof

By growing and processing magnetic iron tetroxide particles in situ on the boron nitride network structure, the problem of low thermal conductivity of boron nitride in the epoxy resin matrix is ​​solved, and efficient thermal conductivity improvements are achieved.

CN119684949APending Publication Date: 2025-03-25HUIZHOU SANDAO NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Boron nitride, as a thermal filler, has a low thermal conductivity in the epoxy resin matrix, and lacks functional groups on the surface, making it difficult to form a uniform dispersion, which limits the further improvement of the thermal conductivity of the composite material.

Method used

Through the preparation process, magnetic iron tetroxide particles are grown in situ on the boron nitride network structure and the surface is processed to increase interfacial compatibility and dispersion, and the particle orientation arrangement is achieved using an external magnetic field to form an efficient thermal conduction path.

Benefits of technology

It significantly improves the thermal conductivity of thermally conductive glue in the epoxy resin system, achieves a better continuous thermal conductivity path, and enhances the thermal conductivity of the composite material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses heat-conducting glue as well as a preparation process and application thereof, and belongs to the technical field of heat-conducting glue. Comprising the following steps: mixing curdlan, a pore forming agent, boron nitride powder and deionized water, and calcining to obtain a material A; carrying out surface modification treatment on the material A to obtain a material B; taking the material B to generate magnetic iron in situ to obtain a material C; carrying out surface hydroxylation treatment on the material C to obtain a material D; and enhancing the interfacial compatibility of the material E to obtain a material F, and preparing to obtain the heat-conducting glue with excellent heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive glue, and in particular relates to a thermal conductive glue and a preparation process and application thereof. Background Art

[0002] With the increasing voltage level of power grid and the increasing lightness of electrical equipment, pure epoxy resin is increasingly difficult to meet the needs of industrial applications. Problems such as electrical failures and insulation failures caused by overheating are becoming more and more frequent. Improving its thermal conductivity has been a problem that has received much attention in recent years. Adding high thermal conductivity fillers is a reliable method to improve the thermal conductivity of epoxy resin. Typical fillers can be divided into metal materials (such as Ag, Al, etc.), carbon-based materials (such as carbon fiber, graphite), ceramic materials (such as boron nitride, silicon carbide, aluminum oxide, silicon oxide and zinc oxide), etc. Among them, boron nitride materials are widely used due to their excellent insulation and thermal conductivity. Adding them as fillers to epoxy resin matrix can effectively solve the problem of low thermal conductivity of the matrix, and they are currently very ideal insulating and thermally conductive fillers. However, the surface of boron nitride materials lacks functional groups that can be used for chemical bonding and interaction. The residual hydroxyl and amino groups on their edges are very few and the chemical activity is very low. It is difficult to form a uniform dispersion in the polymer matrix, which limits the further improvement of the thermal conductivity of the composite material. Summary of the invention

[0003] The purpose of the present invention is to provide a thermally conductive glue and a preparation process and application thereof, so as to solve the problem of low thermal conductivity when boron nitride is added as a thermally conductive filler into an epoxy resin matrix.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A preparation process of a thermally conductive adhesive comprises the following steps:

[0006] S1. Mix curdlan, pore-forming agent, boron nitride powder and deionized water, disperse by ultrasonic, heat and stir in a water bath, cool, dry and calcine to obtain material A;

[0007] S2, taking the material A, concentrated sulfuric acid and concentrated nitric acid, mixing, ultrasonically oscillating, adding deionized water, stirring, standing at 80° C. for 30-40 hours, centrifuging, washing and drying the solid phase to obtain material B;

[0008] S3, taking the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mixing, ultrasonically dispersing, transferring to a hydrothermal reactor, standing in an oven at 175-185°C for 10-15h, cooling, washing, magnetic separation, and vacuum drying to obtain material C;

[0009] S4, taking the material C and the ethanol solution, mixing, ultrasonically dispersing, adjusting the pH to 3.1-3.3, stirring, filtering, and vacuum drying the solid phase to obtain material D;

[0010] S5, deionized water, propanol, acetonitrile, and tetramethylammonium hydroxide were mixed, stirred, aminopropyltriethoxysilane was added, heated in a water bath with stirring, precipitated, filtered, and the solid phase was dried to obtain material E;

[0011] S6, take deionized water and isopropanol and mix them, add the material D, adjust the pH to 12-14, perform ultrasonic oscillation, add the material E, heat and stir in a water bath, centrifuge, wash the solid phase, dry, grind, and sieve to obtain material F;

[0012] S7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, heated and stirred, and the material F is added and ultrasonically dispersed to obtain the thermal conductive glue.

[0013] As a preferred technical solution of the present invention, in step S1, the mass ratio of the curdlan, the pore-forming agent, the boron nitride powder and the deionized water is 1.5-1.7:7-9:4.5-6.5:80-100.

[0014] As a preferred technical solution of the present invention, in step S2, the dosage ratio of material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 5-7g:50-60mL:140-150mL:50-60mL.

[0015] As a preferred technical solution of the present invention, in step S3, the mass ratio of material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1-1.2: 1-2: 77-78: 6.2-6.4: 2-3: 20-30.

[0016] As a preferred technical solution of the present invention, in step S4, the dosage ratio of the material C and the ethanol solution is 3-4g:200mL.

[0017] As a preferred technical solution of the present invention, in step S5, the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide and aminopropyltriethoxysilane is 90g:35-40mL:10-12mL:0.5-0.8g:105-115g.

[0018] As a preferred technical solution of the present invention, in step S6, the dosage ratio of deionized water, isopropanol, material D, and material E is 25-35 mL: 25-35 mL: 1.8-2.2 g: 4.3-7.1 g.

[0019] As a preferred technical solution of the present invention, in step S7, the mass ratio of the epoxy resin, the curing agent, the accelerator, and the material F is 100:7.2-7.5:0.7-0.9:8.7-11.3.

[0020] The thermally conductive glue is prepared using the above-mentioned preparation process.

[0021] The application of the thermally conductive glue refers to the use of the thermally conductive glue to prepare a thermally conductive substrate.

[0022] Beneficial effects of the present invention:

[0023] The thermal conductive glue disclosed in the present invention and its preparation process and application are prepared by preparing a three-dimensional boron nitride network structure as the main body, and in situ growing magnetic ferroferric oxide particles on its surface to increase the dispersibility, so that it can be oriented in an external magnetic field, thereby being highly arranged in an epoxy resin system to obtain a better continuous thermal conductive path; in addition, by treating the surface of the ferroferric oxide particles, its interface compatibility and dispersibility in the epoxy resin system are increased, thereby improving the thermal conductive effect. DETAILED DESCRIPTION

[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0025] Example 1

[0026] A method for preparing a thermally conductive adhesive comprises the following steps:

[0027] S1. Mix curdlan, polystyrene microspheres, boron nitride powder and deionized water, perform ultrasonic dispersion for 30 minutes, stir in a water bath at 85°C for 5 minutes, transfer to a mold, cool to room temperature, dry in an oven at 80°C for 10 hours, transfer to a muffle furnace and calcine at 500°C for 15 minutes to obtain material A; the mass ratio of curdlan, polystyrene microspheres, boron nitride powder and deionized water is 1.5:7:4.5:80;

[0028] S2. Mix the material A, concentrated sulfuric acid and concentrated nitric acid, perform ultrasonic oscillation for 4 hours, add deionized water, stir for 30 minutes, stand at 80°C for 30 hours, centrifuge, wash the solid phase, and dry to obtain material B; the dosage ratio of the material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 5g:50mL:140mL:50mL; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the concentrated nitric acid is 68%;

[0029] S3, take the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mix them, ultrasonically disperse them for 30 minutes, transfer them to a hydrothermal reactor, stand them in an oven at 175°C for 10 hours, cool them, wash them, perform magnetic separation, and vacuum dry them at 70°C for 8 hours to obtain material C; the mass ratio of the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1:1:77:6.2:2:20;

[0030] S4, taking the material C and the ethanol solution, mixing, ultrasonically dispersing for 10 minutes, adding hydrochloric acid to adjust the pH to 3.1, stirring for 1 hour, filtering, taking the solid phase and vacuum drying to obtain material D; the dosage ratio of the material C and the ethanol solution is 3g:200mL; the volume fraction of the ethanol solution is 80%; the concentration of the hydrochloric acid is 0.012mol / L;

[0031] S5, take deionized water, propanol, acetonitrile, tetramethylammonium hydroxide, mix, stir for 30 minutes, add aminopropyltriethoxysilane, heat and stir in a water bath at 50°C for 10 hours, precipitate, filter, take the solid phase and dry to obtain material E; the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide and aminopropyltriethoxysilane is 90g:35mL:10mL:0.5g:105g;

[0032] S6. Mix deionized water and isopropanol, add the material D, adjust the pH to 12, perform ultrasonic oscillation for 30 minutes, add the material E, heat and stir in a water bath at 50°C for 3 hours, centrifuge, wash the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material F; the dosage ratio of deionized water, isopropanol, material D, and material E is 25 mL: 25 mL: 1.8 g: 4.3 g;

[0033] S7. In a vacuum atmosphere, mix the epoxy resin, curing agent and accelerator, stir at 60°C for 1h, add the material F, and ultrasonically disperse for 20min to obtain the thermal conductive adhesive; the mass ratio of the epoxy resin, curing agent, accelerator and material F is 100:7.2:0.7:8.7; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from accelerator DMP-30.

[0034] Example 2

[0035] A method for preparing a thermally conductive adhesive comprises the following steps:

[0036] S1. Mix curdlan, polystyrene microspheres, boron nitride powder and deionized water, perform ultrasonic dispersion for 35 minutes, stir in a water bath at 85°C for 7 minutes, transfer to a mold, cool to room temperature, dry in an oven at 80°C for 11 hours, transfer to a muffle furnace and calcine at 550°C for 20 minutes to obtain material A; the mass ratio of curdlan, polystyrene microspheres, boron nitride powder and deionized water is 1.6:8:5.5:90;

[0037] S2. Mix the material A, concentrated sulfuric acid and concentrated nitric acid, perform ultrasonic oscillation for 5 hours, add deionized water, stir for 35 minutes, stand at 80°C for 35 hours, centrifuge, wash the solid phase, and dry to obtain material B; the dosage ratio of the material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 6g:55mL:145mL:55mL; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the concentrated nitric acid is 68%;

[0038] S3, take the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mix them, ultrasonically disperse them for 35 minutes, transfer them to a hydrothermal reactor, stand them in an oven at 180°C for 12 hours, cool them, wash them, perform magnetic separation, and vacuum dry them at 70°C for 9 hours to obtain material C; the mass ratio of the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1.1:1.5:77.5:6.3:2.5:25;

[0039] S4, taking the material C and the ethanol solution, mixing, ultrasonically dispersing for 13 minutes, adding hydrochloric acid to adjust the pH to 3.2, stirring for 1.5 hours, filtering, taking the solid phase and vacuum drying to obtain material D; the dosage ratio of the material C and the ethanol solution is 3.5g:200mL; the volume fraction of the ethanol solution is 80%; the concentration of the hydrochloric acid is 0.012mol / L;

[0040] S5. Mix deionized water, propanol, acetonitrile and tetramethylammonium hydroxide, stir for 35 min, add aminopropyltriethoxysilane, heat and stir in a water bath at 50°C for 11 h, precipitate, filter, and dry the solid phase to obtain material E; the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide and aminopropyltriethoxysilane is 90 g: 38 mL: 11 mL: 0.65 g: 110 g;

[0041] S6, take deionized water and isopropanol, mix, add the material D, adjust the pH to 13, ultrasonic oscillate for 35 minutes, add the material E, heat and stir in a water bath at 50°C for 4 hours, centrifuge, wash the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material F; the dosage ratio of deionized water, isopropanol, material D, and material E is 30mL:30mL:2.0g:5.7g;

[0042] S7. In a vacuum atmosphere, take the epoxy resin, curing agent and accelerator and mix them, stir at 65°C for 1.5h, add the material F, and ultrasonically disperse for 25min to obtain the thermal conductive glue; the mass ratio of the epoxy resin, curing agent, accelerator and material F is 100:7.4:0.8:9.0; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from accelerator DMP-30.

[0043] Example 3

[0044] A method for preparing a thermally conductive adhesive comprises the following steps:

[0045] S1. Mix curdlan, polystyrene microspheres, boron nitride powder and deionized water, perform ultrasonic dispersion for 40 minutes, stir in a water bath at 85°C for 8 minutes, transfer to a mold, cool to room temperature, dry in an oven at 80°C for 12 hours, transfer to a muffle furnace and calcine at 600°C for 25 minutes to obtain material A; the mass ratio of curdlan, polystyrene microspheres, boron nitride powder and deionized water is 1.7:9:6.5:100;

[0046] S2. Mix the material A, concentrated sulfuric acid and concentrated nitric acid, perform ultrasonic oscillation for 6 hours, add deionized water, stir for 40 minutes, stand at 80°C for 40 hours, centrifuge, wash the solid phase, and dry to obtain material B; the dosage ratio of the material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 7g:60mL:150mL:60mL; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the concentrated nitric acid is 68%;

[0047] S3, take the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mix them, ultrasonically disperse them for 40 minutes, transfer them to a hydrothermal reactor, stand them in an oven at 185°C for 15 hours, cool them, wash them, perform magnetic separation, and vacuum dry them at 70°C for 10 hours to obtain material C; the mass ratio of the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1.2:2:78:6.4:3:30;

[0048] S4, taking the material C and the ethanol solution, mixing, ultrasonically dispersing for 15 minutes, adding hydrochloric acid to adjust the pH to 3.3, stirring for 2 hours, filtering, taking the solid phase and vacuum drying to obtain material D; the dosage ratio of the material C and the ethanol solution is 4g:200mL; the volume fraction of the ethanol solution is 80%; the concentration of the hydrochloric acid is 0.012mol / L;

[0049] S5, take deionized water, propanol, acetonitrile, tetramethylammonium hydroxide, mix, stir for 40min, add aminopropyltriethoxysilane, heat and stir in a water bath at 50°C for 12h, precipitate, filter, take the solid phase and dry to obtain material E; the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide and aminopropyltriethoxysilane is 90g:40mL:12mL:0.8g:115g;

[0050] S6. Mix deionized water and isopropanol, add the material D, adjust the pH to 14, perform ultrasonic oscillation for 40 minutes, add the material E, heat and stir in a water bath at 50°C for 5 hours, centrifuge, wash the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material F; the dosage ratio of deionized water, isopropanol, material D, and material E is 35 mL: 35 mL: 2.2 g: 7.1 g;

[0051] S7. In a vacuum atmosphere, mix the epoxy resin, curing agent and accelerator, stir at 70°C for 2h, add the material F, and ultrasonically disperse for 30min to obtain the thermal conductive glue; the mass ratio of the epoxy resin, curing agent, accelerator and material F is 100:7.5:0.9:11.3; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from Wuhan Baiyite Chemical Co., Ltd.

[0052] Comparative Example 1

[0053] A method for preparing a thermally conductive adhesive comprises the following steps:

[0054] S1. Mix curdlan, polystyrene microspheres, boron nitride powder and deionized water, perform ultrasonic dispersion for 35 minutes, stir in a water bath at 85°C for 7 minutes, transfer to a mold, cool to room temperature, dry in an oven at 80°C for 11 hours, transfer to a muffle furnace and calcine at 550°C for 20 minutes to obtain material A; the mass ratio of curdlan, polystyrene microspheres, boron nitride powder and deionized water is 1.6:8:5.5:90;

[0055] S2, take the material A, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mix them, ultrasonically disperse them for 35 minutes, transfer them to a hydrothermal reactor, stand them in an oven at 180°C for 12 hours, cool them, wash them, perform magnetic separation, and vacuum dry them at 70°C for 9 hours to obtain material C; the mass ratio of the material A, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1.1:1.5:77.5:6.3:2.5:25;

[0056] S3, taking the material C and the ethanol solution, mixing, ultrasonically dispersing for 13 minutes, adding hydrochloric acid to adjust the pH to 3.2, stirring for 1.5 hours, filtering, taking the solid phase and vacuum drying to obtain material D; the dosage ratio of the material C and the ethanol solution is 3.5g:200mL; the volume fraction of the ethanol solution is 80%; the concentration of the hydrochloric acid is 0.012mol / L;

[0057] S4, take deionized water, propanol, acetonitrile, and tetramethylammonium hydroxide, mix, stir for 35 minutes, add aminopropyltriethoxysilane, heat and stir in a water bath at 50°C for 11 hours, precipitate, filter, take the solid phase and dry to obtain material E; the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide, and aminopropyltriethoxysilane is 90g:38mL:11mL:0.65g:110g;

[0058] S5. Mix deionized water and isopropanol, add the material D, adjust the pH to 13, perform ultrasonic oscillation for 35 minutes, add the material E, heat and stir in a water bath at 50°C for 4 hours, centrifuge, wash the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material F; the dosage ratio of deionized water, isopropanol, material D, and material E is 30 mL: 30 mL: 2.0 g: 5.7 g;

[0059] S6. In a vacuum atmosphere, mix the epoxy resin, curing agent and accelerator, stir at 65°C for 1.5h, add the material F, and ultrasonically disperse for 25min to obtain the thermal conductive glue; the mass ratio of the epoxy resin, curing agent, accelerator and material F is 100:7.4:0.8:9.0; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from accelerator DMP-30.

[0060] Comparative Example 2

[0061] A method for preparing a thermally conductive adhesive comprises the following steps:

[0062] S1. Mix curdlan, polystyrene microspheres, boron nitride powder and deionized water, perform ultrasonic dispersion for 35 minutes, stir in a water bath at 85°C for 7 minutes, transfer to a mold, cool to room temperature, dry in an oven at 80°C for 11 hours, transfer to a muffle furnace and calcine at 550°C for 20 minutes to obtain material A; the mass ratio of curdlan, polystyrene microspheres, boron nitride powder and deionized water is 1.6:8:5.5:90;

[0063] S2. Mix the material A, concentrated sulfuric acid and concentrated nitric acid, perform ultrasonic oscillation for 5 hours, add deionized water, stir for 35 minutes, stand at 80°C for 35 hours, centrifuge, wash the solid phase, and dry to obtain material B; the dosage ratio of the material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 6g:55mL:145mL:55mL; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the concentrated nitric acid is 68%;

[0064] S3, taking the material B and the ethanol solution, mixing, ultrasonically dispersing for 13 minutes, adding hydrochloric acid to adjust the pH to 3.2, stirring for 1.5 hours, filtering, taking the solid phase and vacuum drying to obtain material D; the dosage ratio of the material B and the ethanol solution is 3.5g:200mL; the volume fraction of the ethanol solution is 80%; the concentration of the hydrochloric acid is 0.012mol / L;

[0065] S4, take deionized water, propanol, acetonitrile, and tetramethylammonium hydroxide, mix, stir for 35 minutes, add aminopropyltriethoxysilane, heat and stir in a water bath at 50°C for 11 hours, precipitate, filter, take the solid phase and dry to obtain material E; the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide, and aminopropyltriethoxysilane is 90g:38mL:11mL:0.65g:110g;

[0066] S5. Mix deionized water and isopropanol, add the material D, adjust the pH to 13, perform ultrasonic oscillation for 35 minutes, add the material E, heat and stir in a water bath at 50°C for 4 hours, centrifuge, wash the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material F; the dosage ratio of deionized water, isopropanol, material D, and material E is 30 mL: 30 mL: 2.0 g: 5.7 g;

[0067] S6. In a vacuum atmosphere, mix the epoxy resin, curing agent and accelerator, stir at 65°C for 1.5h, add the material F, and ultrasonically disperse for 25min to obtain the thermal conductive glue; the mass ratio of the epoxy resin, curing agent, accelerator and material F is 100:7.4:0.8:9.0; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from accelerator DMP-30.

[0068] Comparative Example 3

[0069] A method for preparing a thermally conductive adhesive comprises the following steps:

[0070] S1. Mix curdlan, polystyrene microspheres, boron nitride powder and deionized water, perform ultrasonic dispersion for 35 minutes, stir in a water bath at 85°C for 7 minutes, transfer to a mold, cool to room temperature, dry in an oven at 80°C for 11 hours, transfer to a muffle furnace and calcine at 550°C for 20 minutes to obtain material A; the mass ratio of curdlan, polystyrene microspheres, boron nitride powder and deionized water is 1.6:8:5.5:90;

[0071] S2. Mix the material A, concentrated sulfuric acid and concentrated nitric acid, perform ultrasonic oscillation for 5 hours, add deionized water, stir for 35 minutes, stand at 80°C for 35 hours, centrifuge, wash the solid phase, and dry to obtain material B; the dosage ratio of the material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 6g:55mL:145mL:55mL; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the concentrated nitric acid is 68%;

[0072] S3, take the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mix them, ultrasonically disperse them for 35 minutes, transfer them to a hydrothermal reactor, stand them in an oven at 180°C for 12 hours, cool them, wash them, perform magnetic separation, and vacuum dry them at 70°C for 9 hours to obtain material C; the mass ratio of the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1.1:1.5:77.5:6.3:2.5:25;

[0073] S4, taking the material C and the ethanol solution, mixing, ultrasonically dispersing for 13 minutes, adding hydrochloric acid to adjust the pH to 3.2, stirring for 1.5 hours, filtering, taking the solid phase and vacuum drying to obtain material D; the dosage ratio of the material C and the ethanol solution is 3.5g:200mL; the volume fraction of the ethanol solution is 80%; the concentration of the hydrochloric acid is 0.012mol / L;

[0074] S5. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, stirred at 65° C. for 1.5 h, material D is added, and ultrasonic dispersion is performed for 25 min to obtain the thermal conductive adhesive; the mass ratio of the epoxy resin, curing agent, accelerator and material D is 100:7.4:0.8:9.0; the epoxy resin is epoxy resin E51, purchased from Jinan Jumeihui Chemical Co., Ltd.; the curing agent is polyamide curing agent 650, purchased from Zhongshan Yuanda New Materials Co., Ltd.; the accelerator is accelerator DMP-30, purchased from accelerator DMP-30.

[0075] The thermally conductive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were respectively transferred to a polytetrafluoroethylene mold (12.7 mm×12.7 mm×2 mm), and high-temperature resistant parallel magnets were respectively placed 10 cm above and below the polytetrafluoroethylene mold. The molds were cured at 100-110° C. for 2-4 h and cooled to room temperature to obtain a thermally conductive adhesive film with a uniform thickness of 150 μm.

[0076] The thermal conductive adhesive prepared in Example 2 was transferred to a polytetrafluoroethylene mold (12.7 mm×12.7 mm×2 mm), cured at 100-110° C. for 2-4 h, and cooled to room temperature to obtain a thermal conductive adhesive film with a uniform thickness of 150 μm, as Comparative Example 4.

[0077] Performance Testing

[0078] Test Example 1

[0079] The thermal conductivity of the thermally conductive adhesive films prepared in Examples 1-3 and Comparative Examples 1-4 was tested according to ASTM D5470. The test results are shown in Table 1 below.

[0080] Table 1

[0081] Thermal conductivity (W / m·K) Example 1 11.67 Example 2 11.83 Example 3 11.72 Comparative Example 1 10.73 Comparative Example 2 7.78 Comparative Example 3 9.82 Comparative Example 4 8.57

[0082] As can be seen from Table 1, the thermally conductive glue prepared in Examples 1-3 of the present application has excellent thermal conductivity; the present application prepares a three-dimensional boron nitride network structure as the main body, and in situ grows magnetic ferroferric oxide particles on its surface to increase dispersibility, so that it can be oriented in an external magnetic field, thereby being highly arranged in the epoxy resin system to obtain a better continuous thermal conduction path; in addition, by treating the surface of the ferroferric oxide particles, the interfacial compatibility and dispersibility in the epoxy resin system are increased, thereby improving the thermal conductivity effect.

[0083] Test Example 2

[0084] The thermally conductive adhesive film prepared in Examples 1-3 was sandwiched between two 150 μm thick copper foils and vacuum hot pressed at 120-150° C. and 10-30 kgf to obtain a thermally conductive substrate. The breakdown voltage performance test and peel strength test were performed. The test results are shown in Table 2 below.

[0085] Table 2

[0086] Withstand voltage(KV) Peel strength (N / mm) Example 1 5.88 4.14 Example 2 5.93 4.25 Example 3 5.91 4.22

[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A preparation process of thermal conductive glue, characterized in that: The following steps are involved: S1. Mix curdlan, pore-forming agent, boron nitride powder and deionized water, disperse by ultrasonic, heat and stir in a water bath, cool, dry and calcine to obtain material A; S2, taking the material A, concentrated sulfuric acid and concentrated nitric acid, mixing, ultrasonically oscillating, adding deionized water, stirring, standing at 80° C. for 30-40 hours, centrifuging, washing and drying the solid phase to obtain material B; S3, taking the material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water, mixing, ultrasonically dispersing, transferring to a hydrothermal reactor, standing in an oven at 175-185°C for 10-15h, cooling, washing, magnetic separation, and vacuum drying to obtain material C; S4, taking the material C and the ethanol solution, mixing, ultrasonically dispersing, adjusting the pH to 3.1-3.3, stirring, filtering, and vacuum drying the solid phase to obtain material D; S5, deionized water, propanol, acetonitrile, and tetramethylammonium hydroxide were mixed, stirred, aminopropyltriethoxysilane was added, heated in a water bath with stirring, precipitated, filtered, and the solid phase was dried to obtain material E; S6, take deionized water and isopropanol and mix them, add the material D, adjust the pH to 12-14, perform ultrasonic oscillation, add the material E, heat and stir in a water bath, centrifuge, wash the solid phase, dry, grind, and sieve to obtain material F; S7. In a vacuum atmosphere, epoxy resin, curing agent and accelerator are mixed, heated and stirred, and the material F is added and ultrasonically dispersed to obtain the thermal conductive glue.

2. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S1, the mass ratio of the curdlan, the pore-forming agent, the boron nitride powder and the deionized water is 1.5-1.7:7-9:4.5-6.5:80-100.

3. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S2, the dosage ratio of material A, concentrated sulfuric acid, concentrated nitric acid and deionized water is 5-7 g: 50-60 mL: 140-150 mL: 50-60 mL.

4. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S3, the mass ratio of material B, anhydrous ferric chloride, ethylene glycol, anhydrous sodium acetate, polyethylene glycol 600, and deionized water is 1-1.2: 1-2: 77-78: 6.2-6.4: 2-3: 20-30.

5. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S4, the dosage ratio of the material C and the ethanol solution is 3-4 g: 200 mL.

6. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S5, the dosage ratio of deionized water, propanol, acetonitrile, tetramethylammonium hydroxide and aminopropyltriethoxysilane is 90g:35-40mL:10-12mL:0.5-0.8g:105-115g.

7. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S6, the dosage ratio of deionized water, isopropanol, material D, and material E is 25-35 mL: 25-35 mL: 1.8-2.2 g: 4.3-7.1 g.

8. The preparation process of a thermally conductive adhesive according to claim 1, characterized in that: In step S7, the mass ratio of the epoxy resin, the curing agent, the accelerator, and the material F is 100:7.2-7.5:0.7-0.9:8.7-11.

3.

9. A thermally conductive adhesive obtained by the preparation process according to any one of claims 1 to 8.

10. An application of the thermally conductive adhesive as claimed in claim 9, characterized in that: The application refers to preparing a thermally conductive substrate using the thermally conductive glue.